2014
DOI: 10.1016/j.ajhg.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing of 2,000 Danish Individuals and the Role of Rare Coding Variants in Type 2 Diabetes

Abstract: In the original Supplemental Data available for download on November 27, 2013, the graphs in Figures S14-S16 and S18-S20 were unfortunately missing data because of a technical error during file conversion. The Supplemental Data file has been corrected online and is currently available for download. The authors regret the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 0 publications
0
67
0
1
Order By: Relevance
“…We also assessed the allele frequency data of identified variants derived from an available 'control' exome data set provided by NHLBI Exome Variant Server (EVS, http://evs.gs.washington.edu/EVS/) and the Danish exome study. 24 For the RPE65 variants deposited in the RPE65 LOVD, we also assessed their prevalence using the Exome Aggregate Consortium (ExAC) database (http:// exac.broadinstitute.org). Five computational prediction programs, SpliceSite finder-like, 25 MaxEntScan, 26 NNSPLICE, 27 Gene Splicer 28 and Human Splicing Finder 29 were used to determine the pathogenic effect of noncanonical splice variants.…”
Section: Pathogenicity Interpretation Of Sequence Variantsmentioning
confidence: 99%
“…We also assessed the allele frequency data of identified variants derived from an available 'control' exome data set provided by NHLBI Exome Variant Server (EVS, http://evs.gs.washington.edu/EVS/) and the Danish exome study. 24 For the RPE65 variants deposited in the RPE65 LOVD, we also assessed their prevalence using the Exome Aggregate Consortium (ExAC) database (http:// exac.broadinstitute.org). Five computational prediction programs, SpliceSite finder-like, 25 MaxEntScan, 26 NNSPLICE, 27 Gene Splicer 28 and Human Splicing Finder 29 were used to determine the pathogenic effect of noncanonical splice variants.…”
Section: Pathogenicity Interpretation Of Sequence Variantsmentioning
confidence: 99%
“…Developments in genotyping and sequencing technologies have further enabled the study of lowfrequency and rare genetic variation [18,21,22]. However, given that most loci contribute only modest effects in the studied populations, the sample sizes required to obtain sufficient statistical power are enormous, reaching >500,000 European or Asian individuals.…”
Section: Gwas In Population Isolatesmentioning
confidence: 99%
“…More work is required to estimate the amount of pleiotropic selection on trait-altering variation before we can assert that rare alleles may play a substantial role in shaping trait variation for many important human phenotypes. Genome-wide rare variant association studies (RVAS) have often been used in an attempt to bound the variance explained by rare alleles for complex traits (Lohmueller et al 2013;Holmen et al 2014;Igartua et al 2015). In this study design, researchers scan the genome (or exome) for rare causal alleles with one or more RVATs and report that rare alleles are unlikely to be a driver of variance in the trait if no signal (or very few signals) are found.…”
Section: Cold Spring Harbor Laboratory Press On May 7 2018 -Publishementioning
confidence: 99%
“…Although studies of complex phenotypes have often suggested that most genetic variance is attributable to common variants of weak effect (Yang et al 2010;Lohmueller et al 2013;Gaugler et al 2014;Igartua et al 2015), recent work has implicated rare variants as a non-negligible source of variance for traits such as height (Yang et al 2015) and prostate cancer (Mancuso et al 2015). With many large-scale sequencing studies underway in an effort to discover the heritable basis of complex traits, it is imperative that geneticists be able to robustly identify association signals in this deluge of noisy data (Maher et al 2012).…”
mentioning
confidence: 99%